Evaluation of role of vitamin-D levels in osteoporosis - Prasad, Shambhu; B. P., Sharma; Saurabh, . (International Journal of Advances in Medicine, 2017)
Background: Osteoporosis is a serious, worldwide, and growing health problem; WHO has estimated the 30% of all women, older than 50 years (post-menopausal) has osteoporosis. Osteoporosis is a skeletal disorder characterized by compromised bone strength predisposing a person to an increased risk of fracture. Bone strength reflects the integration of two main features: bone density and bone quality. Methods: After clinical examination, patients were subjected to lab and radiological investigation as under: complete hemogram with ESR, serum calcium, phosphate, alkaline phosphatase, parathyroid hormone, 25 (OH) vitamin-D, KFT, LFT, DEXA scan. From above data, vitamin-D levels DEXA scan (t-score) was collected and statistically analysed. Results: 53 radiologically established cases by DEXA score (spine) of osteoporosis/osteopenia and 50 persons in control group of the age and sex match with normal DEXA score, presenting to OPD of central institute of orthopaedics, VMMC and Safdarjung Hospital were selected. The mean vitamin D3 level in cases was 19.37ng/ml with standard deviation of 10.2. Range of serum vitamin D3 levels in cases was from 7 to 51.2. Whereas mean vitamin D3 level in control group was 25.92 ng/ml with standard deviation of 7.24. Range of serum vitamin D3 levels in controls was from 10 to 35.5. The mean vitamin D levels of cases and control was 19.735±10.2 and 25.92±7.2 ng/ml respectively, these values were compared by using student t test and results were found to be statistically significant (P= 0.0001). The mean T score in spine cases was -2.59 with standard deviation of 0.92. Range of T score in cases was from -5.1 to -1. Whereas, mean T score in control group was -0.26 with standard deviation of 0.68. Range of T score in controls was from -0.9 to 1.4. The mean T score spine of cases and controls was -2.59±0.92 and -0.264±0.68 respectively, these values were compared by using student t test and results were found to be statistically significant (P = 0.0001). Conclusions: Study recommend that, vitamin D supplementation should be given to patients with osteopenia/osteoporosis. Further prospective studies to firmly establish the relationship between vitamin D and osteoporosis as well as evaluation of vitamin D supplementation in osteoporosis are needed.